International trade and the world economy - Marrewijk, Charles van (Oxford University Press, 2002)
International Trade and the World Economy provides an up-to- date theoretical and empirical analysis of the structure and forces underlying all 'real' international economics, such as trade flows, investment flows, and trade policy. The book is organized into four parts: introduction and classical trade; neo-classical trade; new trade; and new interactions (in geographical economics, multinationals, growth and development, and applied trade policy).